Generic and disease-specific quality of life among youth and young men with Hemophilia in Canada. Issue 1 (December 2016) - St-Louis, J.; Urajnik, D.; Ménard, F.; Cloutier, S.; Klaassen, R.; Ritchie, B.; Rivard, G.; Warner, M.; Blanchette, V.; Young, N.
Abstract Background This study was undertaken to explore the longitudinal patterns of health-related quality of life (HRQoL) among youth and young adults with Hemophilia A (HA) over a 3-year period. This report presents the baseline characteristics of the study cohort. Methods Males, 14 to 29 years of age, with predominantly severe HA were recruited from six treatment centres in Canada. Subjects completed a comprehensive survey. HRQoL was measured using: the CHO-KLAT2.0 (youth), Haemo-QoL-A (young adults) and the SF-36v2 (all). Results 13 youth (mean age = 15.7, range = 12.9-17.9 years) and 33 young adults (mean age = 23.6; range = 18.4 -28.7 years) with moderate (7 %) and severe (93 %) HA were enrolled. All were on a prophylactic regimen with antihemophilic factor (Helixate FS®) during the study. The youth had minimal joint damage (mean HJHS = 5.2) compared to young adults (mean HJHS = 13.3). The mean HRQoL scores for youth were: 79.2 (SD = 11.9) for the CHO-KLAT, and 53.0 (5.5) and 52.3 (6.8) for the SF-36 Physical Component Summary (PCS) and Mental Component Summary (MCS) scores respectively. The mean HRQoL scores for young adults were: 85.8 (9.5) for the Haemo-Qol-A, and 50.8 (6.4) and 50.9 (8.8) for PCS and MCS respectively. PCS and MCS scores were comparable to published Canadian norms, however significant differences were found for the domains of Physical Functioning and Bodily Pain. The disease-specific HRQoL scores were weakly correlated with the PCS for youth (CHO-KLAT vs. PCSr  = 0.28, p  = 0.35); and moderately correlated for the MCS (r  = 0.39, p  = 0.19). Haemo-QoL-A scores for young adults were strongly correlated with the PCS (r  = 0.53, p  = 0.001); and weakly correlated with the MCS (r  = 0.26, p  = 0.13). Joint status as assessed by HJHS was correlated with PCS scores. A history of lifelong prophylaxis resulted in better PCS but worse MCS scores. Conclusion Despite having hemophilia, the youth in this cohort have minimal joint disease and good HRQoL. The young adults demonstrated more joint disease and slightly worse HRQoL in the domains of physical functioning and pain. The data presented here provide new information to inform the selection of Health Related Quality of Life (HRQoL) instruments for use in future clinical trials involving persons with hemophilia. Trial registration ClinicalTrials.gov :NCT01034904 . Study funded by CSL Behring Canada.